2007
DOI: 10.1213/01.ane.0000256974.84535.7a
|View full text |Cite
|
Sign up to set email alerts
|

An Intraatrial Thrombus and Pulmonary Thromboembolism as a Late Complication of Percutaneous Vertebroplasty

Abstract: Although percutaneous vertebroplasty is a simple and generally safe method for the management of vertebral compression fractures, cement leakage outside the vertebral body is a potential source of serious complications. We report a patient who presented with dyspnea and edema five years after percutaneous vertebroplasty and underwent open-heart surgery. This case demonstrates an intraatrial thrombus and pulmonary thromboembolism caused by venous leakage of polymethylmethacrylate as a late complication of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 13 publications
0
30
0
1
Order By: Relevance
“…Many serious complications with this procedure have been reported, including: leakage of, or acute respiratory failure associated with, polymethyl methacrylate; radiculopathy; spinal cord compression; pedicle fracture; pulmonary embolism intra-arterial thrombus; aortic aneurysm; aortic embolism of cement; pyogenic spondylitis; epidural and subdural cement leakage; posterior spinal epidural abscess; and infected vertebroplasty. [13][14][15][16][17][18][19][20] Although the procedure has a quite high success rate in providing immediate and significant pain relief, Yang et al reported that 22 patients with PVP required revision surgery upon presentation of new symptoms postoperatively. 21 The major complication rate associated with PVP is less than 1%, but 16.6% of patients experienced new-onset VCF after PVP during the 24-78-month follow-up period in our previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many serious complications with this procedure have been reported, including: leakage of, or acute respiratory failure associated with, polymethyl methacrylate; radiculopathy; spinal cord compression; pedicle fracture; pulmonary embolism intra-arterial thrombus; aortic aneurysm; aortic embolism of cement; pyogenic spondylitis; epidural and subdural cement leakage; posterior spinal epidural abscess; and infected vertebroplasty. [13][14][15][16][17][18][19][20] Although the procedure has a quite high success rate in providing immediate and significant pain relief, Yang et al reported that 22 patients with PVP required revision surgery upon presentation of new symptoms postoperatively. 21 The major complication rate associated with PVP is less than 1%, but 16.6% of patients experienced new-onset VCF after PVP during the 24-78-month follow-up period in our previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Beside PMMA-cement embolism, a concomitant fatty bone marrow embolism might be discussed as a potential cofactor, since the insertion of cement volume inevitably causes some expulsion of bone marrow [17]. Cement propagation via paravertebral veins into the inferior vena cava and pulmonary embolism has been described in several case reports as possible cause for hypotension, arrhythmia, and hypocapnia [17][18][19][20][21]. In our particular case, the beginning of the clinical symptoms was 30 min after completion of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…One case report presented evidence of thrombus attached to bone cement retrieved from the right atrium nearly five years post vertebroplasty. [9] Endovascular or surgical removal is indicated in patients with evidence of cardiac bone cement embolism and hemodynamic compromise. Features favoring percutaneous removal include fragments that are small and linear.…”
Section: Discussionmentioning
confidence: 99%